Handbook of personality disorders : theory and practice - Magnavita, Jeffrey J. (J. Wiley, 2004)
This comprehensive reference, edited by one of the leading experts in the field, assimilates the newest and most effective treatment techniques for the personality disorders. Each chapter is written by leading scholars in the Cognitive-Behavior, Humanistic and Integrative theoretical models. In addition to a detailed case example in each chapter, additional case studies are integrated and used throughout.